High-structure versus low-structure cooperative learning in introductory psychology classes for student teachers: Effects on conceptual knowledge, self-perceived competence, and subjective task values. (August 2017) - Supanc, Marina; Völlinger, Vanessa A.; Brunstein, Joachim C.
Abstract: Using group presentation classes as a control condition, in nine introductory psychology classes we examined the impact of high-structure versus low-structure cooperative learning on N = 259 student teachers' conceptual knowledge, on their self-perceived competence, and on their appraisals of task values. To vary the structure, we first created a lesson plan built upon core principles of cooperative learning, and then eliminated from this plan critical elements structuring students' shared learning. Two-level analyses revealed that students in the two cooperative conditions (a) did better on three knowledge tests administered throughout the course of this one-semester project, (b) developed a more favorable view of their subject-specific competence, and (c) appraised the utility and intrinsic value of task assignments more positively than did the control students. In each of the three knowledge tests, students in high-structure groups outperformed students in low-structure groups. These findings support the hypothesis that structuring procedures enhance the efficaciousness of cooperative learning methods in college classes. Highlights: Structure-building elements (SBEs) optimize cooperative learning (CL) in college. SBEs accentuate the principles of participant interdependence and accountability. This study had 3 conditions: Structure high vs. low, and an active control group. CL enhanced students' knowledge, felt competence, and task related attitudes. High-structure CL produced by far the greatest knowledge gains.